MXene-containing pressure sensor based on nanofiber film and spacer fabric with ultrahigh sensitivity and Joule heating effect. Issue 11 (June 2022) - Li, Han; Cao, Jiqiang; Chen, Junli; Li, Yonggui; Liu, Jinkang; Du, Zhaoqun
As an important branch of wearable electronics, pressure sensors have the properties of stability, accurate signal transmission and strong durability, and can quickly respond to the compression deformation of the human body, which is essential to intelligent wearable textiles. Here, we fabricated a smart wearable textile called the MXene-containing pressure sensor with both sensing and electrothermal properties, in which the MXene nanofiber film is used as the electric heating layer, and the spacer fabric coated with MXene is used as the pressure layer. After electrospinning, MXene was successfully adhered to the surface of the pressure layer by polyacrylonitrile as a nanofiber film, which shows excellent Joule heating properties. The novel structure enables high sensitivity (508.79 kPa −1, from 1 to 5 kPa; 29, 397.97 kPa −1, from 12 to 35 kPa), good electric heating (over 70°C under 18 V), high breathability (mesh structure) and shock absorption because of the reticulated spacer fabric. There are many potential applications, such as smart insoles, cushions and mattresses, and in this work smart insoles were fabricated for monitoring human motions whether in walking or running. Another applied device is a numeric keyboard, which can recognize finger presses as different numbers. Overall, we provide a new strategy for the fabrication of a multifunctional MXene/spacer fabric-based pressure sensor, and may encourage the innovation of intelligent tactile textiles, which have potential applications in modern medicine and robot protection.